If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-34=-4y+3y
We move all terms to the left:
-34-(-4y+3y)=0
We add all the numbers together, and all the variables
-(-1y)-34=0
We get rid of parentheses
1y-34=0
We add all the numbers together, and all the variables
y-34=0
We move all terms containing y to the left, all other terms to the right
y=34
| 12+x=2(x-4) | | (5x+15)=(3x+21) | | -6x+3=4x+8 | | -11=2y-15 | | 2/3d=4/10 | | -6v+10=2(v-7) | | -5x+4(2-15)=3 | | 9x2−9x−1=0 | | 5(u-2)-7u=-14 | | 15x-31=11x+13 | | 127+(2x41)=180 | | y=-58+2 | | 12x-3x+87=12x+54 | | 4x2−6x+2=0 | | -2.9+4.2z=4.6 | | 15x–31=11x+13 | | −5x2−15x+10=0 | | 23=6=+c | | .02w=1.8 | | 10s-44=8s+6 | | y+-16=12 | | 8x+21=2x+93 | | X=-10x-4 | | 42x-1=64x | | 3s-70=2s-3 | | 7x13x=10 | | 9x-17=4x+23 | | 13s-18=-16 | | 19+28v=-23 | | 12.71+0.14(x+2)=13.21+0.14 | | a+(-28)=0 | | T=0.18s0.52 |